2016
DOI: 10.24925/turjaf.v4i8.684-691.753
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation for Biofortifying The Maize Grain

Abstract: The maize germplasm variation is valuable for breeders to develop elite hybrids with increased mineral contents in the maize grain to eliminate mineral malnutrition, which is referred as HIDEN HUNGER. Therefore, we aimed to determine mineral element diversity of maize landraces collected from different geographical regions of Turkey. There was huge diversity for all mineral traits and other quality traits. Turkish maize landraces showed high variation for Zn (17-41.34 mg kg-1), Fe (13.52-29.63 mg kg-1), Cu (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Literature review revealed that Turkish maize landraces have been screened for agro-morphological traits (Öner and Gülümser, 2014;Kızılgeçi et al, 2018) and some major and minor quality traits (Cömertpay et al, 2016;Ünlü et al, 2018) but they have not yet been evaluated in terms of phytic acid and phenolic compounds. Scientific literature also lacks information on the inheritance of these traits.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review revealed that Turkish maize landraces have been screened for agro-morphological traits (Öner and Gülümser, 2014;Kızılgeçi et al, 2018) and some major and minor quality traits (Cömertpay et al, 2016;Ünlü et al, 2018) but they have not yet been evaluated in terms of phytic acid and phenolic compounds. Scientific literature also lacks information on the inheritance of these traits.…”
Section: Introductionmentioning
confidence: 99%